ENT 530 Social Media Portfolio: Sparkle Hope 365 / Farzana Hazierah Mohd Fareed Faheim - Mohd Fareed Faheim, Farzana Hazierah (2021)
“Slow the Flow, Save H2O” is our tagline here in Sparkle Hope 365 and with the #SparkleHope365 also #MakeAChange hashtag will tell you a story of how we make a change to a better world. The main objective for the business is to offer eco-friendly items that we use on our daily basis as day by day our earth is getting worst because of human activity. We offer you a product that will make a huge transformation in the future. We started our online business on 19th December 2020 using 100% base on social media. Our target customer is students, workers and individuals that are concern about our planet as the main purpose the product is invented are to reduce pollutions and save the earth. Our transportation from us to the customers are mostly using courier services and cash on delivery for the one who is close by. Customers are welcome to directly contact us via WhatsApp if they have any question to ask or even interested to buy our products, we will gladly guide them step by step to satisfy them and make them feel welcomed. One of our best seller products is the customisable name on tumbler where they can put their own name to make it more stylish. Sparkle Hope 365 has still been supported non-stop by our beloved customers and we are grateful for it.